2022
DOI: 10.3389/fendo.2022.977971
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chinese herbal compounds on ocular fundus signs and vision in conventional treated-persons with non-proliferative diabetic retinopathy: A systematic review and meta-analysis

Abstract: BackgroundChanges in fundus signs and loss of visual acuity are an important basis for screening and treating diabetic patients with retinopathy, and conventional Western medicine is moderately effective in treating diabetic retinopathy(DR),To systematically evaluate the effectiveness and safety of Chinese herbal compounds(CHCs) in the combined treatment of diabetic retinopathy.MethodSix electronic databases, including PubMed, were searched to screen eligible literature. Randomized controlled trials of non-pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The previously published meta-analysis [ 9 , 11 , 48 , 49 ] proved that CPMs combined with western medicine is better than western medicine alone in the treatment of DR. However, the curative effects of various CPMs were not horizontally compared and ranked.…”
Section: Discussionmentioning
confidence: 99%
“…The previously published meta-analysis [ 9 , 11 , 48 , 49 ] proved that CPMs combined with western medicine is better than western medicine alone in the treatment of DR. However, the curative effects of various CPMs were not horizontally compared and ranked.…”
Section: Discussionmentioning
confidence: 99%
“…For example, polysaccharide compounds from algae were shown to be non-toxic at concentrations ranging from 100 μg/mL to the minimal effective dose of 0.1 μg/mL [ 172 ]. Furthermore, a meta-analysis by Li et al reported of the safety of Chinese herbal compounds for the treatment of DR, with a significantly lower probability of adverse risks than in the conventional treatment group [ 173 ]. However, cellular and animal models may not fully predict human toxicological outcomes.…”
Section: Mechanisms Of Action Toxicity and Drug–drug Interactions Of ...mentioning
confidence: 99%
“…Calcium Dobesilate ROB Wang Y,2023 [30] 26 2047 CDDP Usual care/placebo Jadad Scale Sun W,2022 [31] 45 9503 TCM Usual care ROB Li XD,2022 [32] 27 2144 TCM+Control Usual care ROB Zhao SY,2022 [33] 1549 Integrated Traditional Chinese and Western Medicine…”
Section: Western Medicine Robmentioning
confidence: 99%